Self-compacting concrete: a comparison between the workability properties, density, porosity and mechanical properties - Stanciu, Darius (2013)
This paper highlights some connections between the workability properties of self-compacting concrete and the density of the concrete mass and between mechanical properties of compression strength and porosity of concrete samples investigated at 28 days of free curing. Also are presented properties of raw materials used in this study.